Involvement of parathyroid hormone-related peptide in the aggressive phenotype of colorectal cancer cells - Novoa Díaz, María Belén (2021)
Colorectal cancer (CRC) remains one of the leading causes of mortality from malignant diseases worldwide. In general terms, CRC presents high heterogeneity due to the influence of different genetic and environmental factors; also, the neoplastic cells are strongly influenced by the extracellular matrix and several surrounding cells, known together as the tumor microenvironment (TME). Bidirectional communication takes place between the tumor and the TME through the release of autocrine and paracrine factors. Parathyroid hormone-related peptide (PTHrP) is a cytokine secreted by a wide variety of tissues and is able to regulate several cellular functions both in physiological as well as in pathological processes. It exerts its effects as a paracrine/autocrine factor, although its mode of action is mainly paracrine. It has been shown that this peptide is expressed by several tumors and that the tumor secretion of PTHrP is responsible for the malignant humoral hypercalcemia. Eight years ago, when our research group started studying PTHrP effects in the experimental models derived from intestinal tumors, the literature available at the time addressing the effects of PTHrP on colorectal tumors was limited, and no articles had been published regarding to the paracrine action of PTHrP in CRC cells. Based on this and on our previous findings regarding the role of PTH in CRC cells, our purpose in recent years has been to explore the role of PTHrP in CRC. We analyzed the behavior of CRC cells treated with exogenous PTHrP, focalizing in the study of the following events: Survival, cell cycle progression and proliferation, migration, chemoresistance, tumor-associated angiogenesis, epithelial to mesenchymal transition program and other events also associated with invasion, such us the induction of cancer stem cells features. This work summarizes the major findings obtained by our investigation group using in vitro and in vivo CRC models that evidence the parti cipation of PTHrP in the acquisition of an aggressive phenotype of CRC cells and the molecular mechanisms involved in these processes. Recently, we found that this cytokine induces this malignant behavior not only by its direct action on these intestinal cells but also through its influence on cells derived from TME, promoting a communication between CRC cells and surrounding cells that contributes to the molecular and morphological changes observed in CRC cells. These investigations establish the basis for our next studies in order to address the clinical applicability of our findings. Recognizing the factors and mechanisms that promote invasion in CRC cells, evasion to the cytotoxic effects of current CRC therapies and thus metastasis is decisive for the identification of new markers with the potential to improve early diagnosis and/or to predict prognosis, to predetermine drug resistance and to provide treatment guidelines that include targeted therapies for this disease.